Arthroscopic lateral collateral ligament imbrication for the treatment of posterolateral rotatory elbow instability - Christos Koukos, MD, PhD; Nikolaos Platon Sachinis, MD, PhD; Konstantinos Sidiropoulos, MD; Michael Kotsapas, MD; Kerem Bilsel, MD, PhD; Fredy Montoya, MD, PhD (JSES International)
Hypothesis: Posterolateral rotatory instability (PLRI) of the elbow is commonly treated with open lateral collateral ligament (LCL) reconstruction techniques. This cohort study evaluates the efficacy of a less invasive arthroscopic LCL imbrication technique for reducing grade I or II PLRI. Methods: Forty-three patients with stage 1 or 2 PLRI, unresponsive to conservative therapy, were included. Diagnoses were based on chronic post-traumatic pain (11 patients), chronic atraumatic lateral elbow pain (20), and previous open tennis elbow surgery (12). Following clinical and arthroscopic diagnosis confirmation, the LCL imbrication technique was performed. The Mayo Elbow Performance Score and range of motion (ROM) were assessed preoperatively and postoperatively using the Shapiro-Wilk test and Wilcoxon signed rank test, respectively, with a minimum 12-month follow-up (range 12-48 months). Results: The Mayo Elbow Performance Score increased significantly from a median of 45 points preoperatively to 90 (range 80-100) at 3 months and 95 (range 80-100) at 12 months follow-up (P < .001). Postoperative median flexion reached 140°, and extension was 0°. At 12 months, 2 patients experienced a 10° extension deficit; 95.3% (41 of 43) achieved full ROM. Knot irritation occurred in 4 patients (out of the first 10 of this cohort, 9.3%), 3 of them requiring knot removal. Switching to a polydioxanone 1 suture eliminated this complication. One patient underwent arthroscopic arthrolysis for adhesions after 14 months. Conclusion: Arthroscopic LCL imbrication offers favorable outcomes for grade I or II PLRI from the third postoperative month with minimal complications. A slight restriction in ROM and transient knot discomfort were the main issues, the latter resolved by switching to a thinner polydioxanone suture.